2018
DOI: 10.1007/978-3-319-94821-8_14
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Mendler-Style Lambda-Encodings in Cedille

Abstract: It is common to model inductive datatypes as least fixed points of functors. We show that within the Cedille type theory we can relax functoriality constraints and generically derive an induction principle for Mendler-style lambda-encoded inductive datatypes, which arise as least fixed points of covariant schemes where the morphism lifting is defined only on identities. Additionally, we implement a destructor for these lambda-encodings that runs in constant-time. As a result, we can define lambda-encoded natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…RelTT may be compared with previous work of Stump et al on Cedille [25], [26], [27]. Both systems aim at a minimalistic extension of a small pure type system as a foundation for type theory.…”
Section: Related Workmentioning
confidence: 99%
“…RelTT may be compared with previous work of Stump et al on Cedille [25], [26], [27]. Both systems aim at a minimalistic extension of a small pure type system as a foundation for type theory.…”
Section: Related Workmentioning
confidence: 99%
“…Next, we consider the first step in our progression towards Cedille's recursion universe. This is a recursion universe for so-called Mendler-style recursion, an approach to terminating recursion originated by Mendler [Mendler 1991], and studied subsequently in a number of other works [Ahn and Sheard 2011;Firsov et al 2018;Vene 1999, 2000]. The basic idea proposed by Mendler is to change the form of algebras from…”
Section: A Mendler-style Recursion Universementioning
confidence: 99%
“…For type families S and T of kind I → ⋆, Cast • I • S • T is the type of generalized identity functions in CDLE; its formation, introduction, and elimination rules are given in Figure 2a. This family of types was first introduced by Firsov et al in [8], wherein it is called Id, and only the non-indexed variant is given (for the related notion of zero-cost coercion in Haskell, see [5]). Since CDLE is Curry-style, an identity function from S to T might exists even if S and T are inconvertible types.…”
Section: Derived Constructsmentioning
confidence: 99%
“…Geuvers [12] showed the impossibility of deriving induction for them in second-order dependent type theory; Firsov and Stump [10] demonstrated how to generically derive the induction principle for them in CDLE. Parigot [27] showed that the Church-style of encoding has no better than linear-time data accessors (such as predecessor for natural numbers); Firsov et al [8] showed how to use the induction principle for a Mendler-style of encoding [24] to define efficient (constant-time) data accessors. Furthermore, Firsov et al [9] show how to further augment this with course-of-values induction, an expressive scheme wherein the inductive hypothesis can be invoked on subdata at unbounded depth.…”
Section: Introductionmentioning
confidence: 99%